Kualitas dan Efektivitas Sistem Layanan Konsumen Mobile Banking (Studi Kasus pada Bank BCA Cabang Malang) - -, Nurniah (Universitas Brawijaya, Indonesia, 2009)
The quality of costumer support system mobile banking involves information supplies, services, and characteristics of the system itself. Its effectiveness is reflected by the satisfaction of its users. The study examines the quality and effectiveness of the costumer support system mobile banking. The objective of this research is analyze the effect of information quality, system quality, and service quality on the costumer support system effectiveness defined as user satisfaction. Data form a survey of 62 mobile banking user of the BCA Cabang Malang are used to test theoretically expected relationships among the variable observed. Sample were puposively selected. Data were analyzed with multiple linear regression model. The result of the study indicate that information, system, and service quality have a significant effect on the user satisfaction. It is concluded that three quality dimensions play the role to determining the effectiveness of costumer support system. In a practical implication, the result are olso offered to the benefits for managers and system designers.Keywords: Mobile Banking; Costumer Support System; Information Quality; System Quality; Service Quality; User Satisfaction